THE IMPORTANCE OF TEACHING LINGUOCOUNTRY STUDY AND TRANSLATION (Intent Research Scientific Journal, 2023)
The main goal of linguistic and cultural studies, as an auxiliary discipline for the practical mastering of the language, and therefore a subject of philological orientation, is to ensure understanding, namely: the transfer of knowledge of culture, the so-called background knowledge, contributing to the full disclosure of the meaning of the statement and its adequate understanding in the act of communication in English and Russian languages. The subject of linguo-cultural studies, which introduces the use of a living language, provides communicative competence in a foreign language, it acts as a linguistic basis not only for linguodidactics, but also for translation, which is singled out as a separate type of speech activity.